Pengaruh Kompensasi Terhadap Kinerja Karyawan Bagian Pabrik Kelapa Sawit (PKS) Studi PT. Sawit Asahan Indah di Kabupaten Rokan Hulu - Dandy Adrian; Rosmayani Rosmayani (Pelantar Press, 2023)
Compensation is something received by employees in lieu of their service contribution to the company. Compensation is an award or reward for workers who have contributed in realizing their goals, through activities called work. Compensation is also an award given by employees, both directly and indirectly, financially and non-financially, to employees for their contribution to achieving organizational goals, so that compensation is needed by the company and to improve the performance of its employees. The purpose of this study was to find out how the provision of incentives and the performance of the employees of the Palm Oil Mill (PKS) at PT. Sawit Asahan Indah Rokan Hulu Regency and its influence. The population in this study were all employees of the palm oil mill (PKS) at PT. Sawit Asahan Indah in Rokan Hulu Regency in 2021 totaling 106 people, while the sample determined using the Slovin formula was obtained as many as 51 people. This research was carried out using a quantitative descriptive method using primary data and secondary data obtained through interviews or research questionnaires. From the research results it is known that the compensation received by the employees is good so that the performance they produce is also good. From the test results it is known that compensation has an effect on employee performance variables at PT. Asahan Indah Oil Palm, Rokan Hulu Regency.